Pharmacovigilance of esketamine nasal spray: an analysis of the FDA adverse event reporting system database - Liu, Ruixue; Liu, Chunxiao; Feng, Dianwei; Guo, Tongxin; Wang, Ying (Frontiers in Pharmacology, 2024)
Esketamine nasal spray (ESK-NS) is a new drug for treatment-resistant depression, and we aimed to detect and characterize the adverse events (AEs) of ESK-NS using the Food and Drug Administration (FDA) adverse event reporting system (FAERS) database between 2019 Q1 and 2023 Q4. Reporting odds ratio (ROR), proportional reporting ratio (PRR), and multi-item gamma Poisson shrinker (MGPS) were performed to detect risk signals from the FAERS data to identify potential ESK-NS–AEs associations. A total of 14,606 reports on AEs with ESK-NS as the primary suspected drug were analyzed. A total of 518 preferred terms signals and 25 system organ classes mainly concentrated in psychiatric disorders (33.20%), nervous system disorders (16.67%), general disorders and administration site conditions (14.21%), and others were obtained. Notably, dissociation (n = 1,093, ROR 2,257.80, PRR 899.64, EBGM 876.86) exhibited highest occurrence rates and signal intensity. Moreover, uncommon but significantly strong AEs signals, such as hand–eye coordination impaired, feeling guilty, and feelings of worthlessness, were observed. Additionally, dissociative disorder (n = 57, ROR 510.92, PRR 506.70, EBGM 386.60) and sedation (n = 688, ROR 172.68, PRR 155.53, and EBGM 142.05) both presented strong AE signals, and the former is not recorded in the Summary of Product Characteristics (SmPC). In clinical applications, close attention should be paid to the psychiatric disorders and nervous system disorders, especially dissociation. Meanwhile, clinical professionals should be alert for the occurrence of AEs signals not mentioned in the SmPC and take preventive measures to ensure the safety of clinical use.